Piece by piece [videorecording (DVD)] - Neville, Morgan; Zeldes, Jason; Wickenden, Aaron; Vazquez, Oscar; Williams, Pharrell; Andrews, Michael, 1967- (Universal, 2024)
It is a unique cinematic experience that invites audiences on a vibrant journey through the life of cultural icon Pharrell Williams. Told through the lens of LEGO animation, turn up the volume on your imagination and witness the evolution of one of music's most innovative minds.